Buddhist Tantric Thealogy? The Genealogy and Soteriology of Tārā - Scherer, Burkhard 1971- (2018)
The-a-logy within the Judeo-Christian tradition can be described as a feminist religious subversion of (hetero)patriarchal theology. In this article I argue that the Buddhist bodhisattva/deity Tārā (Saviouress, Tibetan sgrol ma) can provide (and is indeed already providing) similar empowering counter-patriarchal impulses in contemporary global Buddhist (post-)modernism(s). This article gauges the possibilities of developing thealogy in the Buddhist context based on the unique approach to enlightened female compassion provided in the Indic and Tibetan Mahāyāna and Vajrayā?a traditions. Genealogy, narratives, iconography, and soteriological conceptualization of Tārā in selected Sanskrit and Tibetan stotras (praises) and sādhanas (meditation texts) are discussed. Tārā is demonstrated to be a multi-valent and multi-functional figure within evolving and changing Indic and Tibetan reference frames. The article follows Tārā's transformative journey from her origin in hybridity with (Hindu/Saiva/Sākta) Devī/Durgā traditions; her conceptualization as embodiment of the compassion of Avalokitesvarahimself the (male) bodhisattva of compassion; as the "saviouress from the eight great dangers" (aṣṭa-mahābhaya; Tibetan 'jigs pa chen po brgyad: lions, elephants, fire, snakes, robbery, water dangers, political dangers/prison, and demons/pisācas); to the empowering female bodhisattva, transcending the gender binarism as Princess Ye shes zla ba. Subsequently, Tārā's rise and function within Buddhist Tantra and her connection and identification with Prajñāpāramitā, and as a consort in the Mahāyoga and Yoginī Tantra traditions are scrutinized. I show how identifying with the female deity in tantric practice pushes the heteropatriarchal, male adept beyond the edge of gender binarism and facilitates the collapse of gender dualities into nondual awareness: on every level of the practitioner's weakening dualistic perception of conventional reality, Tārā provides the female access port to nonduality beyond gender. After shedding light on the meaning and the function of Tārā deity yoga in Indo-Tibetan traditions, this article reflects on contemporary "theological" adaptations, such as the New Age Buddhist Tārā dancers, and the challenges and opportunities of Buddhist tantric thealogy. This article exemplifies how a feminist-emancipatory impulse within Christian theology and Christian studies can provide a fruitful inspiration for analogous impulses in Buddhist critical-constructive thought (Dharmology) and Buddhist studies.
Keywords: Buddhist literature; Tārā; Tibetan Buddhism; Feminism; Goddess; Iconography; Modernism; Ritual; Tantra; Thealogy